Latent profile analysis of health literacy in patients with chronic kidney disease and its impact on quality of life - XIAO Ningting; CHEN Lili; YANG Ying; LI Li (Yixue xinzhi zazhi)
Objective To explore the potential categories of health literacy in patients with chronic kidney disease (CKD) and to analyze their impact on patients' quality of life.Methods From April to September 2023, patients with CKD in the inpatient nephrology department of a tertiary-level hospital in Nanchong City were selected by convenience sampling method and surveyed using general information questionnaire, CKD health information literacy questionnaire, and chronic renal failure patients' quality of life measurement scale. Mplus 8.0 software was used to analyze the potential profiles of health literacy, and Logistic regression was used to analyze the influencing factors of quality of life.Results A total of 348 CKD patients were included. The average score for health literacy was (72.44 ± 16.98), and the score for quality of life was (67.46 ± 11.09). The results of the latent profile analysis showed that health literacy could be categorized into “high access-high reserve” (9.19%), “overall moderate” (37.36%), “overall low” (34.48%), and “high access-high integration” (18.97%) categories. The results of multivariate analysis showed that male, age